High, open wedge tibial osteotomy: Finite element analysis of five internal fixation modalities - Stepanović Željko; Živković Miroslav; Vulović Snežana; Aćimović Ljubiša; Ristić Branko; Matić Aleksandar; Grujović Zoran (Vojnosanitetski Pregled)
Background/Aim. Medial open wedge tibial osteotomy is one of the most widely accepted method of treatment for varus knee deformity in younger patient population. Its success depends on the quality of fixation and preservation of the outer cortex of the tibia. The aim of the study was to evaluate stress distribution in five numerically designed plate configurations which can be used in open wedge tibial osteotomy. Methods. The paper describes the 3D numerical model of the tibia with 10° varus deformity correction obtained by an optical scanner ATOS. The simulation anticipated axial compressive loads of 700 N, 1 400 N and 2 100 N. We used a modification of the standard T-plate in all of the five tested models. Modalities were tested with and without a metal block, and with and without a stable angle fixation plates and screws. Software PAK was used in the analysis of stress distribution. Results. With exception for the standard T-plate configuration without the supporting block, the loads up to 1400 N did not result in critical stresses on the outer cortex of the tibia in the remaining four models. There is an objective risk of possible failure of the outer cortex and loss of correction at a load of 2100 N in all configurations. The plate model with the angle stable fixation and the supporting metal block showed the most optimal distribution of stresses on the plate-bone composite compared to other models. Conclusion. The standard T-plate configuration without supporting metal block is not sufficient to stabilize the open wedge osteotomy of the tibia. Numerical models of the angle stable T-plate and the supporting metal block achieved a favorable distribution of stresses on the bone and implant which require further biomechanical testing.